Marginalização Social e Violência - Moliterno , Roberto José; A. Gomes , Carlos Alberto; A. Romano, Rafael; L. B. Vieira, Clarisse Regina; A. C. dos Santos, Dilene; Onofre Gripp, Alexandre; C. Avelar, Fernando; B. Ribeiro, Osmar José (A Defesa Nacional, 2021)
Matéria extraída do relatório elaborado pelo grupo R. participante do Curso de Extensão (CE-11-93) da ESG.